Slovakiaʼs Roma population and unemployment: Does public transport quality matter? - Hluško, Richard; Horňák, Marcel; Polačková, Zuzana (Geografický časopis / Geographical Journal, 2024)
Most of the Roma population in Slovakia have been reportingly facing poverty and social exclusion. Included in this, access to stable jobs has been one of the major issues. Mobility is considered as one of the key prerequisites ensuring access to the labour market. Due to the generally poor economic conditions of the majority of Roma households in Slovakia, public transport is expected to play an important role in Roma populationʼs mobility as a cheap mode of transportation. The paper seeks to reveal the spatial relationship between public transport accessibility and quality, the concentration of the Roma ethnic population, and unemployment rate, thereby highlighting the most vulnerable municipalities in Slovakia. For this purpose, typology of municipalities based on the three mentioned indicators was carried out. Although the quality of public transportation services cannot be considered as the only factor of access to jobs, our intention is to point to the fact that, according to the analyses in the paper below, areas with a low quality of public transport in Slovakia largely correspond with regions of a high unemployment rate and high concentration of the Roma population.